The Future of Automotive Digital Experiences: Transforming Vehicles into Interactive Platforms - Vijay Kumar Cheni (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The automotive industry stands at a digital crossroads where vehicle technology rapidly evolves beyond functional transportation to become a fully integrated digital experience. This article explores three pivotal areas of automotive digital innovation: personalized infotainment systems that adapt to individual driver preferences, voice-first interfaces that enhance safety through natural language interaction, and immersive in-car entertainment that transforms idle travel time into engaging passenger experiences. Examining these systems’ technical architecture, design principles, and integration challenges provides a comprehensive framework for understanding how digital experiences are reshaping the automotive landscape and creating new opportunities for differentiation in an increasingly competitive market.